Effect of Good Corporate Governance and Sustainability Reporting to the Integrated Reporting Moderation Firm Size - Dian Murdianingsih; Agung Prayogi; Tri Handayani (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2022)
The aim of this research is. Analyzing the impact of good governance and its occurrence on integrated reporting with company size as a moderate variable. The research was conducted on mining companies. the period 2019-2021. The research sample was obtained as many as 44 companies with purposive sampling method. The data analysis technique used multiple linear regression, Moderated Regression Analysis. The results of data analysis found that independent commissioner reporting and sustainability had no effect on integrated reporting, and Firm Size is able to moderate the relationship between Good Governance and Sustainability Reporting on integrated reporting. Based on the research results, investors can consider and pay attention to the presence of the audit committee as an internal company before investing.